Improve material handling system in Hirotako Acoustic Sdn.Bhd's : logistic department area - Samylingam, Lingenthiran (2012)
This thesis deals with the improvement of material handling system in Hirotako Acoustics Sdn.Bhd. Logistic Department area. The first objective of this thesis is to reduce the unnecessary movement of the forklift in reducing the travelled distance and eliminate excessive oil usage. The second objective of this project is to reduce the time taken to load and unload racks and also the lead time of delivery. A video recorder was used to record the routines and then the data was analysed through the time study sheet which was provided in the company. Three different experiments were used in order to determine the correlation between the time taken, distance travelled and also oil usage. As result, it has been observed that as the distance decreases, the time taken to load and unload decreases, which indirectly reduced the lead time of delivery. By applying the new method the excessive oil usage can be reduced. As for the recommendation, we need to take into consideration about the time taken, oil usage, cycle time, the distance travels and also the unnecessary motions. So in future, we can measure the above mentioned properties to optimally select a proper material handling system for its specific application. The other alternatives such as electric forklift which consumed less oil and have more advantages than normal forklift also can be considered in order to less the expenses on oil.